2008
DOI: 10.1001/archinte.168.19.2118
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Dizziness and Vertigo in the Community

Abstract: Background: Dizziness and vertigo are common, however, the cause often remains unexplained. The percentage of vertigo of vestibular origin in individuals with unselected dizziness has not been well examined, and its underestimation may lead to diagnostic bias in primary care. The purpose of this study was to reassess the burden of dizziness in the community and to quantify the contribution of vertigo of vestibular origin. Methods: A nationally representative sample of 4869 adults living in Germany was screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
348
5
24

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(399 citation statements)
references
References 32 publications
22
348
5
24
Order By: Relevance
“…As for the syndromic distribution by gender, there was again a significant difference between the two, and the peripheral vestibular syndrome in the female gender was the most frequent, given the concordance with those reported in several studies [5,18,23]. Age groups aged 40 to 59 years and equal to or above 60 years had similar results, although some studies indicate that the majority of individuals complaining of dizziness are the elderly [3,23,24].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…As for the syndromic distribution by gender, there was again a significant difference between the two, and the peripheral vestibular syndrome in the female gender was the most frequent, given the concordance with those reported in several studies [5,18,23]. Age groups aged 40 to 59 years and equal to or above 60 years had similar results, although some studies indicate that the majority of individuals complaining of dizziness are the elderly [3,23,24].…”
Section: Discussionsupporting
confidence: 62%
“…These data do not differ from those found in the literature, which point out that the main causes of otoneurological symptoms are those that affect the peripheral vestibular system [17]. However, attacks of central origin are generally more dangerous and deserve attention [18].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The study also showed that vertigo is recurrent in the vast majority of patients (88%). Vertigo has a considerable individual and social impact, causing interruption of daily activities in 40% of affected individuals, sick leave in 41% and avoidance of leaving the house in 19% according to a recent survey [ 44 ].…”
Section: Epidemiology Of Vertigomentioning
confidence: 99%
“…Loss of vestibular function can be a debilitating condition that causes imbalance, unsteady vision, and a 12‐fold increased risk of falls and fall‐associated morbidity 1. Individuals with vestibular loss have difficulty carrying out activities of daily living such as walking, climbing stairs, and driving, and these individuals report increased dependence on others, reduced productivity, and decreased life satisfaction 2, 3, 4, 5. As with other sensory systems, vestibular function declines with age, and older individuals are disproportionately affected by vestibular loss.…”
Section: Introductionmentioning
confidence: 99%